NATO's air war for Kosovo : a strategic and operational assessment - Lambeth, Benjamin S. (Project Air Force series on Operation Allied Force., 2001)
This text aims to offer a thorough appraisal of Operation Allied Force from a military, political and strategic perspective, calling attention to those issues that are likely to have the greatest bearing on future military policymaking.